Motivation and Self-Regulated Learning as Predictors of Academic Performance in Advanced Medical Students. - Freire, Teresa; Curione, Karina (Spanish Journal of Medical Education, 2026)
This study examines the relationship between motivation, self-efficacy, and self-regulated learning strategies (SRL strategies) in advanced medical students, evaluating their influence on academic performance. The Motivated Strategies for Learning Questionnaire (MSLQ) was used to assess motivational dimensions (Intrinsic Value, Self-Efficacy, Test Anxiety) and cognitive, metacognitive, and resource management strategies. Results show that high-performing students exhibit higher levels of self-efficacy, intrinsic value, and use of metacognitive and resource management strategies, such as time and study environment management, effort regulation, and organization. Correlational analyses indicate that motivation enhances the application of effective strategies and that self-efficacy predicts engagement in self-regulated learning. Semi-structured interviews reveal that high-performing students combine individual and collaborative study, prioritize and manage their time, and adjust their strategies according to academic demands, indicating the use of Pintrich’s self-regulated learning strategies including time and study environment management, effort regulation, metacognitive self-regulation, collaborative learning, and motivational regulation, which contribute to their academic success. These findings highlight the importance of integrating programs that foster motivation and self-regulation to optimize academic performance and the development of clinical competencies in Medicine.